RECONSTRUCTION OF MARRIAGE REGISTRATION POST DECISION OF THE MK RI No. 46/PUU-VIII/2010 Jo PERSPECTIVE OF SHARIA MAQOSHID & POSITIVE LAW - Sugianto & Agus Manurung (JIPOWER : Journal of Intellectual Power, 2024)
Indonesia in the 1945 Constitution of the Republic of Indonesia Article 1 paragraph 3 "Indonesia as a State of Law, that in Law No. 1 of 1974 in conjunction with UUM No. 16 of 2019 concerning Marriage. The position in the registration of marriages is considered to be still a legal problem that develops in the understanding that questions the urgency or importance of a marriage that is not registered. Treatment that looks down on the position of women is certainly increasingly unpopular to be accepted now and in the future. The position of marriage without being recorded in the intention of defrauding the principle of transparency can certainly be seen as an irresponsible act in the current state of the values ​​of public awareness. Moreover, by utilizing the syara' argument which actually does not have a correlation with the prohibition of marriage registration, even all worship activities must represent a form of protection for others. The purpose of this writing is to find out the extent to which the application of the legal consequences of the Constitutional Court's Decision No. 46/PUU-VIII/2010 in terms of the law of marriage registration; and is there an Urgency of Legal Problems regarding the Reconstruction of the Implementation of Marriage Registration so that it can be accepted and applied in society in the Maqoshid Syariah Perspective.